Evaluation of the Level of Anxiety and Future Anxiety in Kafkas Unıversity Faculty of Medicine Interns Physcians During the Covid-19 (Coronavirus) Pandemic - Hülya Çakmur; Gülşen Taşdemir Sancı (Journal of Medical Education and Family Medicine)
Objective: The COVID-19 pandemic, which started on December 31, 2019, with the first case in Türkiye on March 11, 2020, has significantly impacted the education system. The transition from face-to-face to remote learning has particularly disrupted medical faculties and their practical training. This study evaluated the anxiety levels experienced by final-year medical students during the pandemic and their potential effects on their future careers.Methods: This study included 6th-year students from the Faculty of Medicine at Kafkas University during the 2020–2021 academic year. Of the 44 eligible students, 40 participated. The participants completed a sociodemographic form, an internship program questionnaire, the Beck Anxiety Scale, and the Beck Hopelessness Scale. T tests and ANOVA were used to evaluate the differences in scale scores according to demographic characteristics.Results: Of the 40 intern physicians, 45% were aged 23-24 years, 65% were male, 95% were single, and 92.5% had no chronic illnesses. Before the pandemic, educational participation averaged 24–40 hours per week, decreasing to 16–24 hours during the pandemic. The average number of hospital hours per week before the pandemic was 56-72 and increased to over 72 hours after the pandemic. The average Beck Hopelessness Scale score was 7.00 (mild hopelessness), and the average Beck Anxiety Scale score was 33.75 (severe anxiety). Interns aged 25-26 years reported greater anxiety than those aged 27-28 years did.Conclusion: The pandemic has negatively impacted medical education and heightened concerns about the future, underscoring the need to reassess medical training systems and enhance remote education practices.